Influence of a wearer's voice on noise dosimeter measurements - Ryherd, Steven; Kleiner, Mendel; Waye, Kerstin Persson; Ryherd, Erica E. (The Journal of the Acoustical Society of America, 2012)
In recent years, interest in personal noise exposure has expanded beyond a workplace safety measure to become an effective means of investigating physiological effects of the acoustic environment on an individual. This work investigates the effects of the wearer's voice as a possible dominant sound source on body-mounted noise dosimeters and develops methods to improve the application of dosimeter measurements in medium-level noise environments. Subjects experienced a controlled set of acoustic conditions while wearing a dosimeter. In each condition, sound pressure levels were recorded with and without the subject speaking controlled phrases. Three experimental variables were considered-room type, noise type, and noise level. All three variables had a statistically significant effect upon the contribution of speech to a dosimeter measurement; for example, noise level was shown to cause a change in speech contribution by as much as 5.5dB between sequential levels. Based upon the analysis, a method of predicting the decibel contribution of a wearer's voice was developed. The results of this study can be used to estimate the effect of a wearer's voice on dosimeter measurements in medium-level noise environments.